1997
DOI: 10.3168/jds.s0022-0302(97)75996-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of Genetic Parameters for a Test Day Model with Random Regressions for Yield Traits of First Lactation Holsteins

Abstract: A model that contains both fixed and random linear regressions is described for analyzing test day records of dairy cows. Estimation of the variances and covariances for this model was achieved by Bayesian methods utilizing the Gibbs sampler to generate samples from the marginal posterior distributions. A single-trait model was applied to yields of milk, fat, and protein of first lactation Holsteins. Heritabilities of 305-d lactation yields were 0.32, 0.28, and 0.28 for milk, fat, and protein, respectively. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
228
4
36

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(294 citation statements)
references
References 20 publications
26
228
4
36
Order By: Relevance
“…(Gilmour et al, 2002). Random regression models (RRM) were chosen for the genetic analysis of test-day data because RRM are able to model differences in genetic effects across time and, therefore, estimate unique lactation curves for every animal (Jamrozik and Schaeffer, 1997). Random regression test-day models were used to estimate heritability separately for MUN from first lactation, for MUN from second lactation and for MUN from third lactation.…”
Section: Methodsmentioning
confidence: 99%
“…(Gilmour et al, 2002). Random regression models (RRM) were chosen for the genetic analysis of test-day data because RRM are able to model differences in genetic effects across time and, therefore, estimate unique lactation curves for every animal (Jamrozik and Schaeffer, 1997). Random regression test-day models were used to estimate heritability separately for MUN from first lactation, for MUN from second lactation and for MUN from third lactation.…”
Section: Methodsmentioning
confidence: 99%
“…In such a context, Jamrozik and Schaeffer (1997) reported very high heritability estimates using TDM, but negative genetic correlations among test days in early and late lactation when using Ali and Schaeffer (1987) curve to adjust the additive genetic effect, assuming the non-hereditary animal effect constant. Later, Jamrozik et al (1997a and b), using the Wilmink (1987) curve reported more realistic heritability estimates at the beginning and end of lactation, indicating the importance of adequate modeling of the non-hereditary animal effect in random regression models.…”
Section: Introductionmentioning
confidence: 99%
“…Residual variance seems to vary in the course of lactation. Jamrozik and Schaeffer (1997) clearly found higher residual variances for milk yield in the first lactation days in contrast to further lactation. This seems to be similar in the present study and can explain the higher residual variance estimated for the whole lactation (ŝ 2 e 5 5.44) in contrast to the separate sections of lactation (ŝ 2 e 5 4.00, 3.65 and 3.05, respectively), because the first lactation days are not included in the first section (days in milk 30 to 70), but they are included for the whole lactation (days in milk 5 to 230).…”
Section: Lactation Curvesmentioning
confidence: 86%
“…Wood, 1967;Grossman and Koops, 1988;Kirkpatrick et al, 1994;Jamrozik and Schaeffer, 1997;van der Werf, 2001;Sylvestre et al, 2006). Ló pez- Romero and Carabañ o (2003) noted that functions frequently used for the modelling of lactation curves are those proposed by Ali and Schaeffer (1987) or Wilmink (1987).…”
Section: Model I (Fr)mentioning
confidence: 99%